Revision of the Neotropical nursery-web spider genus Thaumasia Perty, 1833 (Araneae: Lycosoidea: Pisauridae: Thaumasiinae) - Da Silva, Estevam L. Cruz; Carico, James E. (Zootaxa, 2012)
The Neotropical spider genus Thaumasia Perty, 1833 is revised. Seven of the known species are redescribed andillustrated: Thaumasia senilis Perty, 1833 (type-species); T. abrahami Mello-Leitão, 1948; T. annulipes F.O. Pickard-Cambridge, 1903; T. argenteonotata (Simon, 1898); T. heterogyna Chamberlin & Ivie, 1936; T. scoparia (Simon, 1888)and T. velox Simon, 1898. Ten new species from the neotropical region are described and illustrated: T. caxiuana sp.nov., T. onca sp. nov., T. diasi sp. nov., T. xingu sp. nov., T. acreana sp. nov., T. caracarai sp. nov., T. peruana sp.nov., T. hirsutochela sp. nov., T. lisei sp. nov. and T. oriximina sp. nov. The types of Thaumasia senilis are assumed tobe lost and neotypes are designated. The males of Thaumasia heterogyna, T. annulipes, T. abrahami and the female ofThaumasia senilis are described and illustrated for the first time. Thaumasia annecta Bryant, 1948 and T. decemguttataMello-Leitão, 1945 are synonyms of Thaumasia velox. Thaumasia argyrotypa Chamberlin & Ivie, 1936 issynonymized with Thaumasia heterogyna. Thaumasia argentinensis Mello-Leitão, 1941 is transferred to Lycosidaeand Thaumasia benoisti Caporiacco, 1954 is a junior synonym of Architis spinipes (Taczanowski, 1874). The types ofThaumasia argyrura Mello-Leitão, 1943, Thaumasia brunnea Caporiacco, 1947, Thaumasia strandi Caporiacco, 1947and Thaumasia rubrosignata (Mello-Leitão, 1943) are juvenile specimens, and those species are considered as speciesinquirendae. The type of Thaumasia niceforoi Mello-Leitão, 1941 was not found and is this is species is considered a nomen dubium.